Interactions Between Dynamic Softening and Strengthening Mechanisms During Hot Forging of a High-Strength Steel - Khan, Makarim; Shahriari, Davood; Jahazi, Mohammad; Morin, Jean-Benoit (Frontiers in Mechanical Engineering, 2021)
Open die forging is a critical step in the manufacturing of a large numbers of components used in transportation and energy industries. Dynamic recrystallization, dynamic transformation and dynamic precipitation take place during the hot deformation processing and significantly affect microstructure conditioning which ultimately influence the service properties of the component. In the present work, using a Gleeble 3800 thermomechanical simulator, the open die forging of a large size ingot made of a modified AISI 6140 medium carbon high strength steel was investigated. Deformation temperatures between 1250 to 950℃ and strain rates from 0.01 to 1 s-1 representative of the actual process were considered in the analysis. The generated true stress-true strain curves were used as a basis for the development of a constitutive model predicting the occurrence of softening and strengthening phenomena as a function of thermomechanical conditions. The corresponding activation energy was determined to be about 374kJ.mol-1 and compared with the values reported in the literature for other high strength steels. Dynamic recrystallization kinetics was studied using the t50 model and the influence of temperature and strain rate are quantified and discussed. Interaction between dynamic precipitation and dynamic recrystallization is discussed and the deformation conditions where such interactions occur were determined. The thermomechanical results were complemented by microstructure examination including laser confocal, field emission scanning electron microscopy, transmission electron microscopy and energy dispersive spectroscopy.